Sexual function and depressive symptoms in young women with low vitamin D status: a pilot study. (September 2016) - Krysiak, Robert; Gilowska, Małgorzata; Okopień, Bogusław
Abstract: Objective: Although vitamin D deficiency is associated with an increased risk of numerous disorders, no previous study has investigated its association with sexual dysfunction. The aim of this study was to investigate female sexual functioning and depressive symptoms in young women with low vitamin D status. Study design: The study included 14 women with vitamin D deficiency, 14 women with vitamin D insufficiency, as well as 14 matched healthy women. All participants of the study completed questionnaires evaluating female sexual functioning (Female Sexual Function Index – FSFI) and the presence and severity of depressive symptoms (Beck Depression Inventory-Second Edition – BDI-II). Results: The total FSFI score was lower while the overall BDI-II score higher in women with vitamin D deficiency, but not in women with vitamin D insufficiency, than in healthy subjects. Compared to women with normal vitamin D status, women with vitamin D deficiency were characterized by lower scores for three domains: sexual desire, orgasm and satisfaction, while women with vitamin D insufficiency were characterized by a lower score only for desire. Desire and in women with vitamin D deficiency also orgasm, sexual satisfaction and the overall FSFI score negatively correlated with 25-hydroxyvitamin D levels. Conclusion: The obtained results indicate that low vitamin D status is associated with abnormal female sexual functioning, the severity of which depends on the degree of vitamin D deficiency.